Pathological Metabolism of Methionine in Malignant Cells Is a Potential Target for the Antitumor Therapy - VS Pokrovskii; DZh Davydov; NV Anufrieva; DD Zhdanov; EM Treshchalina; TV Demidkina; EA Morozova (Клиническая онкогематология)
This review presents the characteristics of the cellular metabolism of methionine, as well as known data on the mechanisms of the development of methionine dependence in malignant cells. The possibilities of using a non-methionine diet for the control of the tumor growth in patients with various forms of cancer are considered. The newest information about methionine-γ-lyase, an enzyme providing elimination of methionine from plasma, is grouped and summarised. Its role as a potential antitumor enzyme is disclosed. Data on methionine-γ-lyase producers, activity of this enzyme, obtained from various sources, and information on tumor models and cell cultures, showing methionine dependence are summarised.